Δ-ferrite transformation mechanism and its effect on mechanical properties of 316H weld metal. (15th November 2020) - Zhao, Langlang; Wei, Shitong; Wu, Dong; Gao, Dianbao; Lu, Shanping
Abstract: The microstructure evolution and mechanical properties of the 316H stainless steel weld metals with different C contents were studied at the aging temperature of 550 °C for different aging holding time. The transformation behavior of δ-ferrite and precipitation mechanisms of M 23 C6 and σ phase in the as-aged weld metal were investigated. The results indicated that for the as-welded weld metal, with increasing C content, the yield and tensile strengths increased, while the elongation decreased owing to the increase of C solid solution strengthening effect. Moreover, both the high δ-ferrite content in low C weld metal and the precipitated M 23 C6 carbide in high C weld metal deteriorated the impact energy obviously. During the aging process, the rapid precipitation of M 23 C6 carbide occurred in δ-ferrite firstly owing to the high diffusion rate of C. Once the carbon is depleted by precipitation of M 23 C6, the slow formation of σ phase occurred through eutectoid transformation (δ → σ + γ) depending on the diffusion of Cr and Mo. Moreover, increasing C content promoted the formation of M 23 C6 carbides and inhibited the formation of σ phase. Therefore, increasing C content accelerated the transformation of δ-ferrite in weld metal during aging process. Furthermore, after a long enough aging time, a transformation from M 23 C6 to σ occurred. The variations of mechanical properties with aging conditions depended to a large extent on the microstructures at different aging conditions. For the low C weld metal aged at 550 °C, with the increase of the aging time, fine M 23 C6 first precipitated, then coarsened, after that σ phase formed, which caused that the yield and tensile strengths first increased, then decreased, and finally increased slightly again. For the medium C weld metal, as the aging time increased, first the depletion of the solid solution C as a result the M 23 C6 precipitation deteriorated the strength, and then the formation of σ phase improved the strength. For the high C weld metal, with the increase of the aging time, the depletion of the solid solution C and the coarsening of the M 23 C6 precipitates deteriorated the strength. Furthermore, with increasing aging time, both the precipitation and coarsening of M 23 C6 and increasing σ phase content deteriorated the elongation and impact energy.